Settlement of Traffic Accident Crimes through the Principle of Restorative Justice in the Sorong City Area - Triatmoko, Ryo Thunder; Sinaulan, Ramlani Lina; Yuhelson, Yuhelson (International Journal of Social Service and Research, 2023)
This study focuses on the first problem of solving traffic accident criminal cases that have been applied in law enforcement and how to reconstruct the ideal traffic accident crime resolution based on a restorative justice approach. The method used in this study is normative juridical research with a research approach in the form of a normative approach. The result of this study is that direct involvement between perpetrators, victims, and communities in solving criminal cases is emphasized in the restorative justice approach. Criminal acts involving traffic accidents can be resolved in accordance with the principles of restorative justice. Because it serves the interests of victims and perpetrators based on two perspectives (victims and perpetrators) in terms of accident crimes, the use of restorative justice is essential. The application of restorative justice in solving criminal cases that prioritizes the interests of victims and perpetrators in finding solutions to crimes and their consequences has been outlined in a circular issued by the Indonesian National Police.  The traditional dynamic between local communities and their governments in fighting crime can be changed by the use of restorative justice in cases involving accidents. Customary institutions are still often used in Sorong City by local communities to resolve conflicts, but Law No. 22/2009 on Traffic and Road Transport has stipulated the threat of criminal penalties for those responsible for traffic accidents. Therefore, the police had to investigate the traffic accident even if the victim's family decided not to prosecute.